A combined experimental and computational study of NHC-promoted desulfonylation of tosylated aldimines. Issue 3 (15th January 2020) - Sun, Fang; Yin, Tingrui; Wang, Yang; Feng, Anni; Yang, Liuqing; Wu, Wenchao; Yu, Chenxia; Li, Tuanjie; Wei, Donghui; Yao, Changsheng
Abstract : NHC-catalyzed mild desulfonylation of tosylated aldimines provides efficient access to aryl nitriles with broad substrate scope. DFT calculations demonstrate that the reaction undergoes multiple stepwise processes. Abstract : NHC-catalyzed desulfonylation of tosylated aldimines provides facile access to aryl nitriles in generally good to excellent yields with good functional group compatibilities under mild reaction conditions. DFT calculations demonstrate that the reaction undergoes multiple stepwise processes including nucleophilic addition of NHC to tosylated imine, formation of an aza-Breslow intermediate, deprotonation, and dissociation of the tosyl group.